Morphological and pathogenic variation among isolates of Rhizoctonia bataticola causing dry root rot of chickpea - S.C. DUBEY*, MARYAM AGHAKHANI and (Indian Phytopathology, 2009)
Twenty-three isolates of Rhizoctonia bataticola (Macrophomina phaseolina) causing dry root rot of chickpea (Cicer arietinum) collected from 10 different major chickpea growing states of India were highly variable in their morphological and cultural characters as well as pathogenicity/ virulence. The virulence analysis of the isolates on a set of chickpea cultivars namely ICC 12441, ICC 11332, ICC 11224, ICC 12450,Pusa 362, BGD 112, Pusa 1103, Pusa 212, Pusa 1088 and BCP 17 under blotter paper as well as sick soil grouped them into 6 pathotypes. The pathotype groups were related to agroecological regions of the country.The most virulent isolate (Rb1 from Bangalore, Karnataka) was fast growing and produced largest sclerotia.A set of cultivars was proposed for the first time for differentiating the pathotypes of R. bataticola causing dry root rot of chickpea.